Small‐Scale Variability of Bottom Oxygen in the Northern Gulf of Mexico. Issue 1 (19th January 2021) - Ruiz Xomchuk, Veronica; Hetland, Robert D.; Qu, Lixin
Abstract: While the occurrence of seasonal bottom hypoxia in the Northern Gulf of Mexico is an extensively studied subject, most research effort has been put on understanding and quantifying hypoxic extent, and little is known about internal variability and short‐term shifts. We use a realistic hydrodynamic model with a simple oxygen parametrization to demonstrate that hypoxia development in the far‐field of the Mississippi plume is subject to physical processes with spatial scales ranging from O (10) to O (100 km) and temporal scales from the near‐inertial period to seasonality. We use a budget decomposition of the oxygen equation to explore patterns. The mean spatial structure of the local rate of change reveals features shaped as oxygen loss rings enclosing oxygenation cores. This structure is mainly a balance between net advection (horizontal and vertical) and sediment oxygen demand. In terms of temporal variability, we found a large near‐inertial signal in advection, following a convergence‐divergence pattern, at all spatial scales, and a strong subinertial signal at smaller scales only. Variability in advection increases with decreasing temporal and spatial scales, consistently with a field rich in instabilities introducing small‐scale, strong anomalies. Through a Reynolds decomposition of the budget, we separate anomalies from the main flow and identify the total vertical perturbation flux as the primary counterbalance to sediment oxygen demand during periods when the hypoxic extent is maintained or destroyed. Vertical flux anomalies manifest as bottom water intrusions into the mid water column, which have been captured by high‐resolution observations. Plain Language Summary: In this study, we explore the internal variability and short‐term shifts in the evolution of seasonal bottom hypoxia, or the dead zone, over the Texas‐Louisiana shelf, West of the Mississippi River delta. We use a realistic hydrodynamic model, with a simplified oxygen equation to simulate oxygen dynamics. We calculate an oxygen budget quantifying the contributions of different processes to its rate of change. In space, we found mean features with scales ranging from 10 to 100 km, and in time, we encountered patterns in advection ranging from a near‐daily signal to a seasonal signal. We found that variability in the budget is caused mostly by advection and to be larger at smaller temporal and spatial scales. This variability is consistent with the abundance of small‐scale circulation features typical during summer in this region of the shelf. Additionally, small‐scale features in vertical oxygen advection, anomalies separated from the mean flow, are responsible for most of the oxygenation of the bottom when the extent of the dead zone is steady or decreasing. These vertical anomalies are simulated as intrusions of bottom water into the mid water column and have been seen in high‐resolution observations. Key Points: Modeled bottom oxygen variability ranges from O (10) to O (100 km) in space and from the near‐inertial period to seasonality in time Main variability in oxygen rate of change is due to small‐scale advection (horizontal and vertical) induced by an eddy‐rich shelf The total vertical perturbation flux is the primary counterbalance to sediment oxygen demand and manifests as bottom water intrusions